Strategic governance for hybrid maritime threats: A hexa-helix model approach - Fakhri Reza; Adi Subiyanto; Sutanto (Economic Military and Geographically Business Review, 2026)
Background: Indonesia's eastern maritime region, despite its immense geostrategic importance, faces persistent defense infrastructure gaps, limited naval presence, and fragmented policy implementation. This study aims to address these challenges by proposing the Hexa-Helix collaboration model as a strategic policy framework for maritime defense reinforcement. Methods: Employing qualitative strategic analysis and literature review, the research elaborates the evolution of innovation collaboration theory from the Triple Helix to a novel Hexa-Helix model tailored to the archipelagic defense context. Findings: Findings indicate that existing maritime defense efforts in Eastern Indonesia are hindered by underdeveloped naval infrastructure, limited local shipbuilding industries, and weak stakeholder integration. The Hexa-Helix model incorporates six key actors: government, navy, academia, industry, society, and media to establish a more inclusive and adaptive defense ecosystem, particularly in high-risk zones such as the Sulu Sea. Conclusion: This study concludes that the Hexa-Helix collaboration model provides an effective governance framework for addressing hybrid maritime threats by integrating defense, innovation, and public engagement across key stakeholders. The model strengthens maritime security and institutional resilience in archipelagic regions facing complex transboundary challenges. Novelty/Originality of this article: The novelty of this study lies in institutionalizing the Navy and media as independent helices, expanding conventional innovation frameworks to address hybrid threats in maritime border areas. The model offers strategic pathways for enhancing Indonesia's maritime sovereignty and fostering sustainable local defense industry growth.